Simplify 5/k + (k+3)/(k+5) .
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,554 answers
starTop subjects are Math, Science, and Business
So simplify 5/k + (k+3)/(k+5), we make the denominator the same for all the terms
5/k+(k+3)/(k+5)
=> [5(k + 5) + k(k+3)]/ k(k+5)
=> [5k + 25 + k^2 + 3k]/k(k+5)
=> (k^2 + 8k + 25)/k(k+5)
=> (k^2 + 8k + 25)/(k^2 + 5k)
The required result is (k^2 + 8k + 25)/(k^2 + 5k)
Related Questions
- How do I simplify (k+3)-(3k-5)?
- 3 Educator Answers
- The equation(k+3)x^2+6x+k = 5, where k is a constant, has two distinct real solutions for x.Show...
- 1 Educator Answer
- The points (2,-3), (3,-2) & (8,k) lie on a straight line. Find k.
- 1 Educator Answer
- Find Limit: Where Limit ('k' approaches Infinity) [ k/(k+1) ]^k ?Problem is how to simplify...
- 1 Educator Answer
- Simplify the expression 2(a -3) + 4b - 2(a -b -3) + 5
- 1 Educator Answer
calendarEducator since 2008
write3,662 answers
starTop subjects are Math, Science, and Social Sciences
Given the expression:
E = 5/k + (k+3)/(k+5)
I am assuming that you need to write the expression as a single ratio.
Then, we need to determine the common denominator.
==> E = 5*(k+5) / k(k+5) + (k(k+3) / k(k+5)
Now we will open the brackets.
==> E = (5k+25)/(k^2+5k) + (k^2 + 3k)/ (k^2 + 5k)
==> E = (5k+25+ k^2 + 3k) / (k^2+5k)
Now we will combine like terms.
==> E = (k^2+8k+ 25) / (k^2 + 5k)